Towards Inhibition of Vif-APOBEC3G Interaction: Which Protein to Target? - Iris Cadima-Couto; Joao Goncalves (Advances in Virology)
APOBEC proteins appeared in the cellular battle against HIV-1 as part of intrinsic cellular immunity. The antiretroviral activity of some of these proteins is overtaken by the action of HIV-1 Viral Infectivity Factor (Vif) protein. Since the discovery of APOBEC3G (A3G) as an antiviral factor, many advances have been made to understand its mechanism of action in the cell and how Vif acts in order to counteract its activity. The mainstream concept is that Vif overcomes the innate antiviral activity of A3G by direct protein binding and promoting its degradation via the cellular ubiquitin/proteasomal pathway. Vif may also inhibit A3G through mechanisms independent of proteasomal degradation. Binding of Vif to A3G is essential for its degradation since disruption of this interaction is predicted to stimulate intracellular antiviral immunity. In this paper we will discuss the different binding partners between both proteins as one of the major challenges for the development of new antiviral drugs.